Roy's Adaptation Model Application in Nursing Care for Pregnant Women With Preeclampsia: Literature Review - Yenny Puspitasari; Budi Santoso; Nursalam Nursalam; Agus Sulistyono (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Incidence of preeclampsia cases is about 5-8% of all pregnancies. This research aims to analyze articles related the application of nursing model in pregnant with preeclampsia. The design of the research used is the literature review, articles collected using search engines such as EBSCO, Sciencedirect, Proquest and Elsevier. The article used was published in 2010-2019. Based on the article collected obtained the results that diagnose preeclampsia while pregnant can cause anxiety and fear increases during pregnancy. Because of this condition, individuals have increased blood pressure so as to develop a pathological nature. The role of nurses in providing therapy according to this model is to focus on human beings as a biopsicosocial creature as a unified and interconnected whole. Further studies are advised consider the effects on various variables by taking into account the random effects and changes in the model with the addition of contextual effects in the analysis.